2008
DOI: 10.3844/ajassp.2008.1808.1811
|View full text |Cite
|
Sign up to set email alerts
|

Density Equation of Bio-Coal Briquettes and Quantity of Maize Cob in Phitsanulok, Thailand

Abstract: One of the most important crops in Phitsanulok, a province in Northern Thailand, is maize. Base on the calculation, the quantity of maize cob produced in this region was approximately 220 kton year-1. The net heating value of maize cob was found to be 14.2 MJ kg-1. Therefore, the total energy over 874 TJ year-1 can be obtained from this agricultural waste. In the experiments, maize cob was utilized as the major ingredient for producing biomass-coal briquettes. The maize cob was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 12 publications
1
19
1
1
Order By: Relevance
“…Thus, the higher the density, the lower the relaxation ratio of the briquette will be and the better the stability of the briquette. Overall, compressed density obtained in both briquette types was less than the range of 0.98 to 1.12 g·cm -3 reported for bio-coal briquettes under moderate pressure (Wilaipon 2008). …”
Section: Resultsmentioning
confidence: 87%
“…Thus, the higher the density, the lower the relaxation ratio of the briquette will be and the better the stability of the briquette. Overall, compressed density obtained in both briquette types was less than the range of 0.98 to 1.12 g·cm -3 reported for bio-coal briquettes under moderate pressure (Wilaipon 2008). …”
Section: Resultsmentioning
confidence: 87%
“…Yumak et al [26] produced briquettes from soda weed (Salsolatragus) to be used as a rural fuel source. [27] and the effects of briquetting pressure on banana-peel briquettes and on banana waste in northern Thailand by Weapon [28]. The study reveal that the pseudo stem briquettes showed higher compressive strength compared with leaves banana briquettes.…”
Section: Raw Materials For Briquettingmentioning
confidence: 99%
“…Based on a moisture content of 15%, the heating value is very close to that mentioned previously. Wilaipon [11] referred an average lower heating value of maize cobs of 14.2 MJ/kg, but the corresponding moisture content was not reported. In summary, the lower heating value of maize cobs is comparable with other crop residues and even above average.…”
Section: Introductionmentioning
confidence: 95%
“…As an example in other regions, Wilaipon [11] reported an energetic potential of maize cobs in Thailand to be of over 12 Mt per year.…”
Section: Introductionmentioning
confidence: 98%